Lymphoplasma Exchange Improves Myasthenia Gravis Exacerbations: A Retrospective Study in a Chinese Center - Ouyang, Song; Yin, Weifan; Zeng, Qiuming; Li, Bijuan; Zhang, Jian; Duan, Weiwei; Li, Yi; Liang, Yong; Wang, Jiaqi; Tan, Hong; Yang, Huan (Frontiers in Immunology, 2022)
Background Lymphoplasma exchange (LPE), a technique combining plasma exchange with leukapheresis, is emerging as promising treatment for autoimmune diseases. Data on the efficacy and safety of LPE in myasthenia gravis (MG) therapy are scarce. In this study, we aimed to comprehensively review the clinical efficacy, safety, and immunological characteristics of LPE therapy in MG patients. Study Design and Methods A Chinese cohort of 276 generalized MG patients in state of exacerbation, including impeding crisis, myasthenia crisis, and preparation for thoracic exsection between January 2014 and December 2020, were evaluated in this study. Results A total of 276 patients with a median age of 45.5 ± 16.7 years underwent a total of 635 LPE sessions. Clinical scales of Quantitative Myasthenia Gravis (QMG) scores, Myasthenia Gravis Specific Manual Muscle Testing (MMT) scores, activities of daily living (ADL) scores, and quality of life (QOL) scores were improved during 4 weeks’ follow-up. Adverse effects occurred in 20 out of 276 patients, with 14 patients having one adverse event each. Independent predictive factors for good response to LPE therapy were symptom onset before LPE therapy ≤3 days and age on LPE therapy <50 years of age. LPE decreased the serum levels of antibodies, immunoglobulins, and complements 4 weeks after the first replacement, with decreased levels of interleukin (IL)-17A and interferon (IFN)-γ and increased level of IL-10. Conclusion LPE is an effective treatment for MG patients in state of exacerbation and preparation for thymectomy. Early use of LPE on early-onset MG may have good therapeutic effects. The potential mechanism for LPE is the polarization of cytokines from IL-17A, IFN-γ, into IL-10.